The Influence Of Work Ethos And Discipline On The Effectiveness Of Organizational Performance In Smp Islam Terpadu Bustanul Ulum Central Lampung - Nur Fathi; Parela, Epi (Utami Publisher, 2025)
This study examines the influence of work ethic and work discipline on organizational performance effectiveness at SMP Islam Terpadu Bustanul Ulum Lampung Tengah, which are essential factors in achieving optimal learning objectives. A strong work ethic encourages teachers and staff to work diligently and responsibly, while work discipline involves adherence to rules and punctuality in executing tasks. By understanding the impact of these two factors, the research aims to identify strategies to enhance educational quality and create a productive work environment. This research location was chosen because of its relevance to the research focus on the influence of work ethic and discipline on the effectiveness of organizational performance. With an adequate organizational structure and number of employees, this junior high school is an ideal location to be used as a sample. The research, which is quantitative in nature with a descriptive approach, will take place from May to July 2024, aiming to provide a systematic and accurate presentation of population’s factsQuantitative analysis results indicate that the work ethic variable (X1) has a 21.4% influence on organizational performance effectiveness (Y) at SMP Islam Terpadu Bustanul Ulum Lampung Tengah, while the work discipline variable (X2) has a greater influence of 60.9%. The third hypothesis test indicates that work ethic (X1) and work discipline (X2) simultaneously influence organizational performance effectiveness (Y) with an R-Squared value of 69.3% and an R value of 0.770, demonstrating a strong relationship between the two variables and an improvement in organizational performance effectiveness at the school.